Theory of high temperature superconductivity - Fujita, Shigeji (Fundamental theories of physics, 2001)
The book describes all basic experimental facts about high temperature superconductivity of materials, with a critical temperature of 30 Kelvin and higher, and explains them microscopically starting with a Hamiltonian followed by step-by-step statistical mechanical calculations. All important theoretical formulas are derived without omitting steps and all basic questions are answered in a manner which is easy to understand. The book is therefore suitable as a textbook for a second-year graduate physics course. Many fresh, and some challenging, ideas are presented and researches in the field are invited to examine the text.